Indian public health standards in primary health centers and community health centers in Shimla District of Himachal Pradesh: A descriptive evaluation - Raman Chauhan; Salig Ram Mazta; Dineshwar Singh Dhadwal; Sumita Sandhu (Wolters Kluwer Medknow Publications, 2016)
Introduction: The health planners in India have visualized primary health centers (PHCs) and community health centers (CHCs) as the key healthcare delivery institutions in rural areas. These centers are supposed to have health manpower, infrastructure, and service delivery as per the Indian public health standards (IPHS) guidelines (2010). Materials and Methods: A cross-sectional study was conducted in seven CHCs and 12 PHCs, randomly selected from eight blocks of Shimla District and evaluated in terms of health manpower, infrastructure, and services from September 2011 to August 2012. Data was collected from the selected units using structured data collection instruments designed by the IPHS. Results: The health centers were assessed according to IPHS guidelines. Outpatient department services and referral services were provided in all the centers studied. No specialist doctor was posted at any of CHCs against a sanctioned strength of at least four (surgeon, physician, obstetrician, and pediatrician) per CHC. In 3 (42.8%) CHCs and 8 (75%) PHCs, no pharmacist was posted. Eight (75%) PHCs did not have any staff nurse posted. Three (42.8%) CHCs and 10 (83.3%) PHCs did not have a laboratory technician. In CHCs, separate labor room was available in 6 (85.7%) whereas a separate laboratory was available in all seven. Separate labor room and laboratory were available in four (25%) PHCs. Conclusions: IPHS guidelines are not being followed at PHC and CHC levels of the district. Health manpower shortage is the key bottleneck in service delivery. Political advocacy is needed to ensure sufficient health manpower availability to deliver quality healthcare.